The Right to a Good Defense: Investigating the Influence of Attorney Type Across Urban Counties for Juveniles in Criminal Court - Zane, Steven N. (Criminal justice policy review, 2021)
Juvenile defendants in criminal court represent an especially vulnerable group for whom quality legal representation is critical. While some juvenile defendants are able to obtain private counsel, indigent defendants are provided an attorney by the government. One long-standing concern is that these court-appointed attorneys are less effective. Using data on juveniles in criminal court across 37 large, urban counties, the present study examines conviction and sentencing outcomes by comparing private counsel, public defenders, and assigned counsel. Results indicate that defendants with public defenders were less likely to be convicted, less likely to be incarcerated in prison, and served shorter prison sentences compared to defendants with assigned counsel. Contrary to hypotheses, however, the effect of attorney type was not conditioned by court urbanism. The findings suggest that public defenders provide effective legal representation for juveniles in criminal court. Research is needed to determine whether this holds across different contexts (e.g., rural).